آثار وأسباب المخدرات الرقمية ومعالجتها من منظور إسالمي - م.م كارزان فقى خليل (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
After the revolution of technology and the Internet in the modern era, and its pros and cons, the phenomenon of digital drugs spread through a number of common Internet sites, which are not less dangerous than conventional drugs. Addiction to any drugs that harms human health and mind prohibited by Islamic law. It has now evolved with the development of the world of technology. It has proved that digital drugs are no less dangerous than conventional drugs and have a mood effect similar to cannabis, cocaine and other drugs. Leading to separation from reality, and reduced focus, and after a period of time begins addicted hallucinations and trembling and convulsions and rapid breathing and heartbeat. The researcher focuses on the definition of digital drugs, the reasons and factors that lead individuals to abuse them, the negative effects on the individual and society, the use of music in treatment, the treatment of disease and addiction, and the treatment of Islamic Sharia.